Modern Trends in Teaching English to ICT Students: Methods and Analysis - Raupova, Laylo; Khursanova, Laylo (MMIT Proceedings, 2024)
In today's fast-paced world, the intersection of language and technology skills is essential. This article aims to study modern directions, methodologies and their analysis in the context of teaching English to students majoring in computer technology. As ICT continues to permeate various aspects of the education system, the impact of science on new and effective pedagogical approaches, digital technologies, and the development of students' language and technical skills is undeniable. The article talks about modern trends in teaching English to students of information technology (ICT).